The use of percussion in therapy: a content analysis of the literature. Issue 4 (1st October 2016) - Matney, Bill
Abstract : People have used percussion instruments to promote health throughout history. Contemporary health practitioners have documented their use of percussion instruments. However, no comprehensive review of this discourse appears to exist in a peer-reviewed journal article. This content analysis study, examining international peer-reviewed literature regarding the use of percussion in therapy, aimed to better understand (a) how many articles, over time, have discussed the use of percussion in therapy; (b) what types of articles were written; (c) what instruments were used; (d) with what populations was percussion used; (e) how percussion was used in therapy; and (f) why percussion was used in therapy. Results suggest an increased interest in the use of percussion for health over time. Investigators have studied percussion use with a broad range of populations, using a variety of research methodologies. The analysis includes categories of therapeutic application and therapeutic function in order to highlight trends in the literature. An intercoder reliability check of 10% of studies suggested acceptable percentage agreement regarding article types, populations, and instrumentation. Recommendations for future research, training, and practice based on instrumentation use, therapeutic applications, and therapeutic functions are offered.